New routes to CSO sustainability: the strategic shift to social enterprise and social investment. Issue 5 (3rd July 2016) - Hailey, John; Salway, Mark
ABSTRACT: The issue of sustainability is becoming more important for civil society, as non-profits, NGOs, and other civil society organisations (CSOs) face a range of political, regulatory, organisational, and financial challenges. This article focuses on the crucial dimension of financial sustainability and the growing awareness of the importance of accessing alternative sources of funds and developing new funding models. These include accessing social investment, using subsidiary businesses to fund programme work, or developing new social enterprises. The article draws on analysis of the funding environment and specific examples to explore the different dimensions of sustainability, and assess why many CSOs are looking to new funding models and alternative routes to sustainability.